Raising kids in the age of algorithms challenges of digital parenting - Mad Baguri, Ezza; Masaad Al Attabi, Dalal Shafi; Teshome Taddese, Esayas; Ahmad, Noorlila; Merkine Gebresilase, Bereket; Pg Petra, Pg Nur Ashikin (IGI Global Scientific Publishing, 2026)
With the development of artificial intelligence (AI) and the hyperconnected world of today, children's lives are becoming increasingly interconnected with technology. Parents understand and responsible the use of technology in raising kids. Although there are many advantages to modern technologies, parents also face many difficutties, including as worries about internet safety and the potential for technological addiction. The objective of this book chapter is to explore the key challenges parents face in managing their children's online activities as AI revolutions have transform ways of living. This research used the PRISMA review process and a meta- literature analysis to assess pertinent literature from the Scopus database, covering the period from 2019 to 2025. The selected papers were analysed thoroughly to uncover the new themes that have been classified as the result. The present study makes a significant contribution to raising the standard of education by enabling parents to mentor their children in the use technology revolution, in line with SDG4.